Determination of stationary region boundary in multiple reference frames method in a mixing system agitated by Helical Ribbon Impeller using CFD - Maryam Sanaie-Moghadam; Mansour Jahangiri; Faramarz Hormozi (Journal of Heat and Mass Transfer Research, 2015)
The multiple reference frames (MRF) method is the most suitable method tosimulate impeller rotation in mixing systems. Precise determination of stationaryand moving zones in MRF method leads to accurate results in mixing performance.In this research, the entire volume of mixing system was divided into two zones.The kinetic energy values were used to distinguish the zones with differentvelocities. The low-velocity zones, close to zero, were considered as the stationaryzone and higher velocities were considered as the moving zone. The standardgeometrical parameters were used for mixing system. The axial velocity and axialflow number were compared with literatures for validation. The values fordimensionless diameter of stationary zone at different Reynolds numbers wereachieved for Newtonian and non-Newtonian fluids that are in agreement withvalues applied in literatures. The results show that the dimensionless diameter ofstationary zone decreases as Reynolds number increases.